Pemasaran Online Melalui E-Tourism, Bauran Pemasaran Jasa Pariwisata Dan Pemosisian Untuk Promosi Pariwisata Daerah Di Indonesia - Diah Pradiatiningtyas (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2014)
Tourism is one sector that generates foreign exchange, equity, employment, and income that will accelerate the development of tourism and regional economic growth and regions income. Tourist visits are indicators of tourism development. The problem that arises then is how to maximize the tourism tourist traffic because conventional marketing no longer reach the community at large, especially outside of Indonesian society. Environmental dynamism evolving rapidly as the impact of globalization makes the role of the Internet become indispensable today. This paper attempts to examine the existing literature to form a concept of promotion of tourism through online marketing via e tourism, tourism services marketing mix and positioning. The method used is literature study with a scope of discussion of the online tourism marketing, tourism services marketing mix and positioning of tourism products. The results obtained from this study is that in order to establish an online marketing business tourism e need to establish tourism by developing tourism products, serial impact generated by the tourism industry, the structure of the tourism industry, the availability of communications and information technology devices. The next thing is to identify the marketing mix of tourist services that includes product, price, location, promotion, people involved, the service process, and physical evidence. The final step is to position the tourism products to gain competitive advantage.   Key Words: websites, marketing, online, promotion, tourism